Appropriate Technologies for Environmental Protection in the Developing World
DOI: 10.1007/978-1-4020-9139-1_25
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation and Strength Characteristics of Biofilm Amended Barrier Soils

Abstract: Experimental work was conducted to investigate the influence of biofilm on the consolidation and strength characteristics of two barrier soils. Biofilm has potential as a low-cost additive for soil stabilization, and it may be formed naturally in landfills throughout the developing world. The EPS-producing bacterium Beijerinckia indica was used to prepare solutions of varying concentration of exopolymeric substances (EPS). These solutions were then used as the molding moisture for compacted specimens of locall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(26 reference statements)
1
1
0
Order By: Relevance
“…The observation that sediments become more compressible (or less stiff) with added micro‐organisms is consistent with some results from Daniels et al. (2009), who showed that C c values increase with increasing amounts of biofilm for a lean clay (with sand‐size grains present) but not for a sand–bentonite mixture (65% sand; 35% bentonite). While their results are inconclusive, our results clarify and affirm that micro‐organisms increase C c .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The observation that sediments become more compressible (or less stiff) with added micro‐organisms is consistent with some results from Daniels et al. (2009), who showed that C c values increase with increasing amounts of biofilm for a lean clay (with sand‐size grains present) but not for a sand–bentonite mixture (65% sand; 35% bentonite). While their results are inconclusive, our results clarify and affirm that micro‐organisms increase C c .…”
Section: Discussionsupporting
confidence: 91%
“…This decrease in porosity with progressive burial results in a decrease in mudstone permeability, where porosity and permeability have a log linear relationship (e.g., Neuzil, 1994, 2019; Reece et al., 2012; Schneider et al., 2011). However, the effects of micro‐organisms on the compression behavior of fine‐grained sediments are poorly constrained (Daniels et al., 2009) and their effects on the permeability of fine‐grained sediments are unexplored.…”
Section: Introductionmentioning
confidence: 99%